تطبيق طريقة سكربت للتعليم التعاوني (Cooperative Script) في فهم المقروء لدى طلاب الفصل الخامس في المدرسة الإبتدائية الإسلامية الحكومية 1 آغام - الهاشم, ذكوان; حسنة, نور; ديوي, يلفي; ريزال, إيكا (Darul Yasin Al Sys, 2023)
Teaching the language in the primary school is one of the preferences for education, just as teaching the Arabic language is whether it is teaching other foreign languages, and it trains students on the language skill that divides teaching the Arabic language inti four skills, they are listening skill,speaking skill, reading skill and writing skill. To improve the reading skill of the students, the training is basic, is introducing them to vocabulary and making a simple sentence, through various types of teaching methods that motivate students and provide a wide space for students to have maximum reading skill or understand texts as soon as possible. The researcher found the type of experimental research in quantitative proximity with the pre and post test design. As for the population and the sample they numbered 42 students, with the sample being 21 students from class 5-b. research tools is a practice test (pre and post test). Based on the results of the research and data analysis, the results of calculating the results of the post-test for the control class that were taught using the tradisional education model, with a rate of 71,42, and the post-test for experimental calss using the script method for cooperative education with a rate of 88,09. This indicates that there are differences in learning outcames in the experimental class and the control class. Thus, in testing the hypothesis with a probability of 5% (0,05), the results of the account T 3,385 and the table T 1,684 were obtained, so that the account T is greater than the table T. The zero hypothesis (Ho) is repeated and the substitution hypothesis (Ha) is accepted. Thus, there is an effect of the cooperative learning script method on reading comprehension among fifth-grade students in the state Islamic primary school 1 Agam.